La aculturación medida por la influencia de las redes sociales en la población adolescente Kichwa Kayambi - Gerenas Escobar, Angela Patricia (2023)
This thesis is focused on analyzing the phenomenon of acculturation in the adolescent population of the Kichwa Kayambi culture, specifically from the Cayambe area. For this, an analytical, deductive and observation method was used, it showed us to analyze in a much more concrete and detailed way the scope of interviews, analysis of viral videos from YouTube channels and surveys. At the same time, qualitative approaches were used, such as interviews, which were carried out with four cultural managers from the Cayambe area, within this same approach, observation was used, for which the most viral videos on YouTube channels were analyzed, taking into account counts a sample of five content creators of Kichwa origin. And within this aspect, the quantitative was used, which included surveys, the same ones that were carried out in the Dolores Cacuango Educational Unit to students from eighth to second grade. The interest in this topic arises based on the latent concern that some communities are aging in the remotest solitude and this is because the younger generations do not feel any interest in continuing to promote culture, since it is seen as something irrelevant and even due to issues of discrimination, they become ashamed of their autochthonous roots, causing the true meaning to be lost. Within the present titling work, relevance is given to certain terminologies of the Kichwa Kayambi culture, which will allow us to know more about this culture, in addition, a synthesis of acculturation and Kichwa Kayambi adolescents is proposed with which the study variables are proposed. From these elements, the description of materials and methods is developed, which will help us to generate the results and discussion section.